(untitled) (Patan Prospective Journal, 2022)
This paper assesses COVID19 scenario total economic cost of COVID19 in Nepal through descriptive statistics and macro econometric model. This paper finds COVID19 as an infectious diseases infecting 5.2 million populations and killing 0.4 million population in the World. Globally, the figures of COVID19 cases are extremely intensive more in G20 countries with higher transmission rate. Similarly, in South Asia, its rate is slow and gradual but it threats India, Bangladesh, Pakistan and Nepal. India is an epic center of COVID19. As a result, there is more than 3 trillion USD economic losses at global level and 540 billion NRs economic loss at national level in Nepal with 402 COVID cases. Its reason was health crisis at individual and national level and nationwide long lockdown. The economic impact of COVID19 was less than national wide lockdown. In the estimation, coefficient of COVID19 is -.407 percent meanwhile coefficient of economic loss due to lockdown is -0.86. Therefore, the COVID19 preventive measure is more counter-productive to national income, national output, aggregate demand and employment than the infection and transmission of COVID19 pandemics. Therefore, the government of Nepal should focus a best resilient policy measure instead of preventive measure to minimize policy counterproductive outcomes at national economy more than COVID19 pandemics for stopping economic recession.